Food system perspective on fisheries and aquaculture development in Asia - Tezzo, Xavier; Bush, Simon R.; Oosterveer, Peter; Belton, Ben (Springer, 2021)
This paper reviews development research and policies on freshwater fish in South and Southeast Asia. We conduct a systematic review of academic literature from three major science-based policy institutions to analyze development research and policies that have accompanied the ongoing transition from freshwater capture fisheries to aquaculture in the region. Using a ‘food fish system’ framework allows for the identification and systematic comparison of assumptions underpinning dominant development policies. We analyze the interrelations between the production, provisioning, and consumption of wild and farmed fish and demonstrate a shift toward food fish systems thinking in the sampled literature. We discuss gaps and weaknesses in the literature, as identified through the application of the food fish systems framework and present an agenda for future research aimed at securing the potential of fish as food.